Subclinical Hypothyroidism on the Elderly - Macedo Silva, Sofia (2018)
Introduction: Subclinical hypothyroidism, defined as an increase of thyroid stimulating hormone levels with normal levels of thyroid hormones, could have a multiorgan impact. There seem to be differences in the elderly (over 65 years of age) which indicate that there should be a different approach in terms of diagnosis and the treatment.Material and Methods: Electronic database search and narrative bibliographical review.Results: Different case studies showing the multiorgan consequences of subclinical hypothyroidism suggest that, in the elderly, there is a minor impact or even a lack of repercussion, especially in those over 80 - 85 years old. Additionally, there is evidence indicating that the levels of thyroid stimulating hormone rise with the age of the patient. The standard treatment, in the beginning, is a low dose of levothyroxine when the levels of thyroid stimulating hormone are over 10.0 mIU/L, when there are noticeable symptoms or positive anti-thyroid antibodies. However, the treatment is not consensual when the levels of thyroid stimulating hormone are between 4.5 and 10.0 mIU/L, in such a way that the TRUST study concluded that no benefits have outcome from treating these patients. Discussion: The non-definition of the reference range and the age gap are the key factors that contribute the most to biased results. However, there is consensus regarding non-treatment of mild thyroid dysfunctions (4.5 - 7.0 mIU/L) in the elderly, particularly above 80 years of age. Nevertheless, for positive anti-thyroid antibodies, suggestive ultrasound changes or iatrogenic side effects, the reference level should be 4.5 mIU/L. Conclusion: The general impact of subclinical hypothyroidism is different in elderly people, meaning that an individualized therapeutic approach and long-term monitoring is the appropriate strategy.